2020
DOI: 10.1002/ccd.28735
|View full text |Cite
|
Sign up to set email alerts
|

Compression of the left mainstem bronchus by patent ductus arteriosus in neonates under consideration for ductal stenting

Abstract: Stent angioplasty of patent ductus arteriosus has been shown to be a viable alternative to operative shunt placement in cyanotic neonates. With broader implementation of this strategy, novel complications are bound to arise. We present a series of cases evaluated for ductal stent angioplasty in which a dilated and torturous ductus arteriosus compressed the left mainstem bronchus. After reviewing our recent experience with ductal stenting and isolated Blalock-Taussig shunts, our best estimate of the incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…6,34 Bronchial compression by a stented duct has also been considered a theoretical complication, especially if the patient has evidence of preexisting bronchial compression from a large and ectatic PDA. 61,62 However, stenting may actually improve bronchial compression by leading to PDA shrinkage, straightening, and lateralization 63 ; therefore, bronchial compression should not necessarily be considered a contraindication to stenting. 13 One of the most common late complications, and a significant driver behind reintervention rates, is neointimal proliferation and resulting stenosis of the stent.…”
Section: Acute Complicationsmentioning
confidence: 99%
“…6,34 Bronchial compression by a stented duct has also been considered a theoretical complication, especially if the patient has evidence of preexisting bronchial compression from a large and ectatic PDA. 61,62 However, stenting may actually improve bronchial compression by leading to PDA shrinkage, straightening, and lateralization 63 ; therefore, bronchial compression should not necessarily be considered a contraindication to stenting. 13 One of the most common late complications, and a significant driver behind reintervention rates, is neointimal proliferation and resulting stenosis of the stent.…”
Section: Acute Complicationsmentioning
confidence: 99%
“…Actual incidence of main bronchial compression caused by the dilated patent ductus arteriosus has not been clearly reported in the literature. Smith et al 4 reported that this incidence should be about 4.6%. Patent ductus arteriosus stenting can be used as an alternative to palliative shunt operation in cyanotic newborns.…”
Section: Discussionmentioning
confidence: 92%
“…Airway proximity to the duct should be noted and although this would not necessarily preclude stenting, vigilance is required during follow-up. In a recent single-centre study, dilated and tortuous ductus arteriosus compressing the left mainstem bronchus was found in 4.6% of cases (3/64) being evaluated for ductal stenting or mBT shunt [11]. Diagnosis of airway compression was made following CT and bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%